2022
DOI: 10.3389/fonc.2022.899837
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ARHGAP4 Expression With Colorectal Cancer Clinical Characteristics and Prognosis

Abstract: BackgroundThis study aims to analyze the correlation between ARHGAP4 in the expression and clinical characteristics of colorectal cancer (CRC), and the influence of ARHGAP4 expression on the prognosis of CRC, and to evaluate whether ARHGAP4 is a potential prognostic oncotarget for CRC.MethodsARHGAP4 was identified using the Gene Expression Omnibus database through weighted gene coexpression network analysis. Using the Gene Expression Profiling Interactive Analysis to perform and analyze the expression and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Previously, ARHGAP4 RNA levels have been found to correlate with survival in CRC presented by The Human Protein Atlas (24). A study published in 2022 using GEPIA consistently found ARHGAP4 expression to correlate with adverse prognosis in CRC (25). A previous study has also found indications that high ARHGAP4 levels by immunohistochemical analysis is an independent predictor for poor prognosis in scirrhous-type gastric cancer (29).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, ARHGAP4 RNA levels have been found to correlate with survival in CRC presented by The Human Protein Atlas (24). A study published in 2022 using GEPIA consistently found ARHGAP4 expression to correlate with adverse prognosis in CRC (25). A previous study has also found indications that high ARHGAP4 levels by immunohistochemical analysis is an independent predictor for poor prognosis in scirrhous-type gastric cancer (29).…”
Section: Discussionmentioning
confidence: 97%
“…The Human Protein Atlas indicates that mRNA expression levels of ARHGAP4 may influence survival in colorectal cancer (24). A prior study using online Gene Expression Profiling Interactive Analysis (GEPIA) found that high levels of ARHGAP4 expression was correlated with adverse prognosis in CRC (25). So far, there is no report exploring the impact of ARHGAP4 expression on patient outcome in CRLM.…”
mentioning
confidence: 99%
“…It has been reported that ARHGAP4 can be a novel regulator of in pancreatic cancer cells [ 34 ]. Moreover, the high expression of ARHGAP4 in colorectal cancer is related to the immune cells such as B cells, CD8 + and CD4 + T cells, macrophages, neutrophils, and dendritic cells [ 35 ]. ARHGAP4 maybe a new target for POR treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific biomarkers for diagnosis, individualized treatment and predicting prognosis of KIRC are still needed to be evaluated. Some investigations have shown that ARHGAP4 is highly expressed in colorectal cancer, gastric cancer and cervical cancer, and is related to tumor progression and prognosis [30,31,32]. Similarly, the expression of ARHGAP4 has a certain effect on the effect of chemotherapy in ovarian tumors [33].…”
Section: Discussionmentioning
confidence: 99%